Incentive Mechanisms for Supplier Development in Mega Construction Projects - Zeng, W.; Wang, H.; Li, H.; Zhou, H.; Wu, Peng; Le, Y. (IEEE, 2018)
IEEE Supplier development (SD) has become an emerging supply chain management practice for firms focusing on their core strategic advantages by outsourcing a significant portion of production or construction activities. Various incentive mechanisms are available for suppliers to improve their capabilities to meet owners & #x2019; expectations. However, a comparative analysis is needed to understand how successful they are. This paper investigates the incentive mechanisms for SD in a construction supply chain that consists of one owner and one supplier. Considering the owner & #x0027;s dominant position in the negotiation of a supply contract, a principal & #x2013;agent model with the objective of optimizing the owner & #x0027;s profit and a Stackelberg game model designed to optimize the profits of both the owner and supplier are proposed and analyzed. Two commonly used incentive methods, including purchase price incentive and cost sharing, are analyzed and compared. The analysis and comparison are illustrated by a numerical example. The primary contribution of this paper is the analysis of the impact of incentive methods on quality improvement for the supplier and a sensitivity analysis of the supplier & #x0027;s internal and external factors, such as purchase quantity, market demand, and manufacturing cost structures, which are useful managerial insights for SD practices in mega construction projects.